Prevalence of impostor syndrome among healthcare students in Saudi Arabia and its association with academic performance - Alrefi, Sara B; Almutairi, Reema M; Almazyad, Sultanah K; AlQarni, Mohammed Dhafer; Alghamdi, Mohammed Abdullaziz; AlDraiwiesh, Ibrahim A; Oyelade, Tope; Alqahtani, Jaber S (Edelweiss Applied Science and Technology, 2024)
Impostor syndrome refers to the inability to internalize accomplishments observed in high-achieving individuals and is linked with persistent anxiety, fear, and stress. The current study aimed to evaluate the prevalence of impostor syndrome (IS) and its association with academic performance among healthcare students in the Kingdom of Saudi Arabia (KSA). This was a cross-sectional study that utilized the Clance Impostor Phenomenon Scale to evaluate impostor syndrome among 620 healthcare students in KSA. Additionally, participants' academic performance was assessed by collecting Grade Point Average (GPA), collected from October 2023 to February 2024. Of the 620 healthcare students surveyed, 380 (61.3%) were female, and 604 (97.5%) were between the ages of 18 and 27. A total of 306 (49.4%) of the respondents reported experiencing high to intense levels of IS. While females have a higher prevalence of high to intense IS than males, this difference was insignificant (p = 0.29). Compared with students with a GPA of 4.5 – 5, the GPA ranges from 2 to 2.74 (OR: 0.168, 95%CI: 0.032-0.888) and 3.75 to 4.49 (OR: 0.032, 95%CI: 0.036-0.864) have relatively lower risk of developing high to intense IS. A high GPA and being from the Western region increase the risk of high to intense IS among healthcare students in KSA. These findings suggest that IS may intensify with academic success and geographical location, irrespective of demographic factors.